SGRP annual report 2003 of the CGIAR System-wide Genetic Resources Programme - CGIAR Systemwide Genetic Resources Programme (2004)
Activities in 2003 continued to build on previous efforts and to launch prominent new initiatives. For example, the growing awareness of the importance of agricultural biodiversity for improved livelihoods and poverty alleviation provided the impetus for SGRP to hold an international meeting on the subject. That in turn resulted in the Conference of the Parties to the Convention on Biological Diversity welcoming the meeting's call for an international facilitation unit to coordinate and develop research on agricultural biodiversity (see page 15). Work to establish the unit is now under way. Efforts to help countries and national partners to come to grips with international policy and law on genetic resources has also received a boost with the publication of a learning module on 'Law and Policy of Relevance to the Management of Plant Genetic Resources' (see page 19). After development and testing, the module has been released so that people with practical management and policy-making responsibilities for plant genetic resources canensure that their governments and institutions are meeting legal requirements and developing appropriate policies. Regionalized versions are now being developed. The Global Crop Diversity Trust has been active too, focusing in particular on issues of governance. An Interim Panel of Eminent Experts was appointed to establish the Trust as an independent international fund (see page 9). While the Trust works for the long-term support of genebanks, SGRP coordinated efforts to secure the immediate upgrades that the genebanks of the Future Harvest Centres need in order to ensure that their activities meet the highest internationally agreed standards. An application to the World Bank for support was granted and the vital process of improving genebank operations has begun in earnest, with considerable results already visible (see page 5). SINGER, the Systemwide Information Network for Genetic Resources, continues to improve access to information about genetic resources (see page 12).